Identification of Rationality and Potential Drug Interactions in Preeclampsia Patients with Comorbidities - Awaluddin, Nurhikma; Zafira Dedy, Nadya Aliyah; Dwi Rantisari, Andi Meinar; Murtiadi, Nadya Nur Aulia (Journal of Food and Pharmaceutical Sciences, 2025)
Preeclampsia is one of the pregnancy complications that constitutes a major cause of maternal and fetal morbidity and mortality. Its management requires the rational and safe use of medications, as there is a potential for drug interactions that may affect therapeutic outcomes. This study aimed to evaluate the rationality of drug use and potential drug interactions in preeclampsia patients in the inpatient ward of Pertiwi Mother and Child Hospital, Makassar. This research employed a descriptive method with a retrospective approach, utilizing medical records of preeclampsia patients from January 2024 to January 2025. The evaluation of rationality was based on the “four rights” principle: right indication, right drug, right dose, and right time of administration. The results of this study showed that the majority of patients received rational pharmacotherapy, with nifedipine being the most commonly used antihypertensive drug. The potential drug interactions identified were predominantly of moderate severity. The findings indicate that, overall, drug use among preeclampsia patients in this hospital has not yet been fully rational, and the presence of potential drug interactions requires careful consideration in clinical practice.